Cote d'Ivoire : 2009 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Nonobservance of Performance Criteria, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that Cote d'Ivoire has embarked on comprehensive reform policies to address the challenges of enhancing growth and reducing poverty. It adopted a Poverty Reduction Strategy Paper in February 2009, which covers the seven-year period 2009-15, and aims to transform the country into an emerging economy. The authorities have strengthened fiscal control and the transparency of budget implementation in recent years while making room to increase pro-poor spending. Significant revenue efforts have facilitated an increase in spending for urgent needs.